2002
DOI: 10.1002/art.10049
|View full text |Cite
|
Sign up to set email alerts
|

Th2‐oriented profile of male offspring T cells present in women with systemic sclerosis and reactive with maternal major histocompatibility complex antigens

Abstract: Objective. To characterize the cytokine production profile of male-offspring T cells reactive against maternal major histocompatibility complex (MHC) antigens present in the peripheral blood and/or skin from women with systemic sclerosis (SSc).Methods. T cell clones were generated from peripheral blood and/or skin biopsy specimens from 3 women with SSc of recent onset and from peripheral blood from 3 healthy women, all of whom had 1 male child. All clones were screened for their proliferative response in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 14 publications
7
80
0
5
Order By: Relevance
“…The T cell clones derived from male offspring T cells of women with SSc were of the Th2 type and produced, in response to maternal MHC antigens, substantially higher levels of IL-4 than did all of the remaining T cell clones derived from the same women. In the remaining T cell clones, the Y chromosome was not detectable, although they responded by proliferation to maternal or allogeneic MHC antigens (137). These results demonstrate that male offspring T cells that are present in small proportions in the skin or in the peripheral blood of women with SSc are able to respond, under appropriate conditions, to maternal MHC antigens and produce Th2 cytokines (137).…”
Section: Putative T Cell Antigens In Sscmentioning
confidence: 80%
See 2 more Smart Citations
“…The T cell clones derived from male offspring T cells of women with SSc were of the Th2 type and produced, in response to maternal MHC antigens, substantially higher levels of IL-4 than did all of the remaining T cell clones derived from the same women. In the remaining T cell clones, the Y chromosome was not detectable, although they responded by proliferation to maternal or allogeneic MHC antigens (137). These results demonstrate that male offspring T cells that are present in small proportions in the skin or in the peripheral blood of women with SSc are able to respond, under appropriate conditions, to maternal MHC antigens and produce Th2 cytokines (137).…”
Section: Putative T Cell Antigens In Sscmentioning
confidence: 80%
“…In the remaining T cell clones, the Y chromosome was not detectable, although they responded by proliferation to maternal or allogeneic MHC antigens (137). These results demonstrate that male offspring T cells that are present in small proportions in the skin or in the peripheral blood of women with SSc are able to respond, under appropriate conditions, to maternal MHC antigens and produce Th2 cytokines (137). The long-term presence of these male offspring T cells in women with SSc supports the notion that long-term microchimerism, manifested as chronic GVHD, may play an important role in the pathogenesis of SSc (137).…”
Section: Putative T Cell Antigens In Sscmentioning
confidence: 98%
See 1 more Smart Citation
“…Initial observations suggested that T cells infiltrating the skin and other organs in SSc were functionally heterogeneous but preferentially polarized towards IFN-γ production and therefore belonging to the Th1-like subset [28]. With the development of more refined techniques and increased knowledge about T cell function, it has become more evident and widely documented that T cells secreting high levels of IL-4 (Th2-like subset) distinctly populate SSc tissues [9,12,25,70,82,99]. These comprise classical CD4+ T helper cells [70,99] but also CD8+ T cells [9] as well as T cells expressing simultaneously CD4 and CD8 and carrying both helper and cytolytic function, together with high production of IL-4 [82].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of more refined techniques and increased knowledge about T cell function, it has become more evident and widely documented that T cells secreting high levels of IL-4 (Th2-like subset) distinctly populate SSc tissues [9,12,25,70,82,99]. These comprise classical CD4+ T helper cells [70,99] but also CD8+ T cells [9] as well as T cells expressing simultaneously CD4 and CD8 and carrying both helper and cytolytic function, together with high production of IL-4 [82]. More recently, CD8+ T cells characterized by high production of IL-13 and expression of GATA-3 have been detected within the repertoire of Btype 2^cells present in SSc peripheral blood and involved skin, particularly during early phases of the disease [35,36,72].…”
Section: Introductionmentioning
confidence: 99%